Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Please halp me solve this.....X=(5y-3)/(y+2)?
I've been looking for how to solve this everywhere! Please please help me, this is for a intermediate algebre class, and it's due tomorrow! thanks
3 Answers
- jimbotLv 61 decade agoFavorite Answer
Since there is one equation with two unknowns, you can't just solve it. Perhaps you meant "express y in terms of x".
x = (5y - 3) / (y + 2)
x(y + 2) = (5y - 3)
xy + 2x - 5y + 3 = 0
y(x - 5) + 2x + 3 = 0
y(x - 5) = -2x - 3
y = (-2x - 3) / (x - 5)
y = (2x + 3) / (5 - x)
- 1 decade ago
Use synthetic division:
The formula for that is Y-K/Whatever the dividend is (in this case it's 5Y-3).
The 2 becomes the value of K in the equation Y-K
Y+2 becomes Y-2 so it is:
Y-2/5Y-3
Bring down the 5 and multiply it by -2 to get -10.
Add -3 to -10 to get -13.
The answer is "5 remainder -13".
- Jeff AaronLv 71 decade ago
Suppose that 5y-3 = a(y+2) + b
Then 5y-3 = ay + (2a+b)
So a = 5 and 2a+b = -3 and therefore b = -13
Therefore (5y-3)/(y+2) = 5 - 13/(y+2)
This isn't necessarily a "solution", just a different way of writing the expression.